Primary bone tumours in Kashmir valley a retrospective histopathological study - Wani, Lateef; Ashai, Farzana Bashir; Banday, Bilal Musharaf; Ashraf, Aadil; Mushtaq, Shaista; Itoo, Mohd. Saleem; Reshi, Ruby (International Journal of Basic and Applied Sciences, 2014)
The present study was carried out in the postgraduate department of Pathology at Government Medical College, Srinagar, India, to study the histopathological pattern of primary bone tumors in Kashmir valley over a period of 15 years.  During this study, 373 histologically proven primary bone tumors were analyzed. Out of these, 298 were benign (79.89%) and 75 were malignant (20.10%). Peak incidence was in the second and third decade of life with male predominance. Among the malignant tumors, the highest incidence was that of Osteosarcoma (52%), followed by Ewing’s sarcoma (24%) and Chondrosarcoma (14%). Osteochondroma (49%) was the most frequent tumor in the benign category. The most commonly affected bones were femur, tibia and humerus in that order. Comparison with similar studies from other parts of the globe indicate  that the  relative frequency of primary bone tumors appears to be low but shows a rising trend in the last 10 years in this part of the world.
Keywords: Benign Bone Tumours; Chondrosarcoma; Hematoxyli; Immunohistochemistry; Osteosarcoma; Soft Tissue Sarcoma.